Green technology of energy-efficient materials up to 70% for plasma display panel - Sutjipto, Agus Geter Edy; -, Jufriadi; Muhida, Riza; Othman, Raihan (2010)
A plasma display panel (PDP) is a type of flat panel display common to large TV displays (32" inches or larger). Many tiny cells between two panels of glass hold a mixture of noble gases. The gas in the cells is electrically turned into a plasma which then excites phosphors to emit light. One of major part in the plasma display panel is its protecting layer. MgO thin film has been widely used as a protective layer for dielectric materials. An addition material to MgO as base material is an alternative method for improving its property as protective layer. A study of reducing the surface discharge potential of single pure MgO protecting layer by the addition of ZrO2 with several compositions is presented. The discharge properties approach taken is by utilizing the flashover treeing for material characterization, produced by a scanning electron microscope (SEM). From the experiment, ZrO2 addition into high purity MgO has influenced the property of MgO. Since secondary electron emission coefficient contributes in increasing the electric field of the surface, it could be found that 5 wt% ZrO2 added MgO has highest secondary electron emission coefficient because the charging and discharging process happened within a shorter time. Therefore comparing with pure MgO, this new material could increase the efficiency of the energy consumption of a plasma display up to 70%.